PRAKTEK MU’ATHAH DALAM TRANSAKSI BA’I KONTEMPORER MENURUT PANDANGAN ABU ZAKARIYA MUHYIDDIN AN-NAWAWI - Nurhasanah; Arfah; Fitriana (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2025)
This study aims to examine how the practice of Mu'athah in Contemporary Ba'I Transactions from the perspective of Abu Zakariya Muhyiddin An-Nawawi. This study is a type of library research or literature research using qualitative methods by conducting content analysis with the Content Analysis model. The results of the study indicate that mu'athah is converted from classical Ba'I to contemporary ba'I. Abu Zakariya Muhyiddin An-Nawawi stated that the practice of Mu'athah is categorized as buying and selling and its law is valid (legal), referring to urf (customs in society) and based on the argument that Allah has permitted buying and selling, in this case there is no specific editorial provision in the sharia and there is not a single hadith that requires ijab qabul in buying and selling, there is no sin in seeking sustenance in the field of commerce, mutual consent, not difficult and there is no prohibition from the Prophet regarding ba'I mu'alahah. Apart from the Koran and Sunnah, another basis for allowing ba'i mu'alahah is the rules of Ushul Fiqh where the law can change with changing situations, conditions and conditions. Ba'i Mu'athah is a commercial transaction that is carried out by the process of taking and handing over goods without saying I sell and I buy (ijab and qabul)